2008
DOI: 10.1002/pst.336
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic parameters estimation using adaptive Bayesian P‐splines models

Abstract: In preclinical and clinical experiments, pharmacokinetic (PK) studies are designed to analyse the evolution of drug concentration in plasma over time i.e. the PK profile. Some PK parameters are estimated in order to summarize the complete drug's kinetic profile: area under the curve (AUC), maximal concentration (C(max)), time at which the maximal concentration occurs (t(max)) and half-life time (t(1/2)).Several methods have been proposed to estimate these PK parameters. A first method relies on interpolating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As such, they commonly fail when used for predictions outside the range of data used to establish them. Examples of these kinds of pharmacokinetic models include those with sum-of-inverse-Gaussian functions to describe drug absorption profiles (Csajka et al 2005) or Bayesian p-splines to estimate pharmacokinetic parameters ( Jullion et al 2009). By contrast, a purely mechanistic model incorporates physiologically based assumptions about the mechanisms controlling the system.…”
Section: 2mentioning
confidence: 99%
“…As such, they commonly fail when used for predictions outside the range of data used to establish them. Examples of these kinds of pharmacokinetic models include those with sum-of-inverse-Gaussian functions to describe drug absorption profiles (Csajka et al 2005) or Bayesian p-splines to estimate pharmacokinetic parameters ( Jullion et al 2009). By contrast, a purely mechanistic model incorporates physiologically based assumptions about the mechanisms controlling the system.…”
Section: 2mentioning
confidence: 99%
“…We develop the corresponding Bayesian inferential methodology using a simple, previously unknown, solution. Spatially adaptive penalty parameters have also been used before (Ruppert and Carroll 2000;Eilers and Marx 2002;Baladandayuthapani, Mallick, and Carroll 2005;Lang and Brezger 2004;Jullion and Lambert 2006;Pintore, Speckman, and Holmes 2006). However, this is the first article to combine these features.…”
mentioning
confidence: 94%
“…The population smooth function in this case, where the basis is not specified, is a thin-plate regression spline (Wood, 2003). Note that the pseudo-logarithmic transformation of 𝑡𝑖𝑚𝑒 allows 𝑡𝑖𝑚𝑒 = 0 to be included (Jullion et al, 2009), but is somewhat non-linear especially for small values of 𝑡𝑖𝑚𝑒, which requires some caution to select an appropriate unit. This corresponds to a group-level model with shared wiggliness, as expressed in Pedersen et al, (2019).…”
Section: Example 1: Application To Descriptive Pharmacokineticsmentioning
confidence: 99%
“…Notably, Park et al, (1997) reported semiparametric modelling using splines, as a convenient and flexible alternative to nonlinear multilevel models, including random effects for between-subject variation. Jullion et al, (2009) described application of Bayesian P-splines, including extensive mathematical details and consideration of priors, with a focus on sparse problems. Most recently, Willemsen et al, (2017) described the application of a specific variant of multilevel spline model to bioequivalence determination with NCA, and nominated several potential advantages, including handling of sparsity and implementation of censoring, which are directly relevant to the HGAM approach evaluated here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation